(untitled) (MAUSAM, 1995)
The electrical conductance (EC) of rain waters at Visakhapatnam is studied for a three year period of 1991-93. Lower amounts of rainfall (RF) record higher conductivity values and vice-versa due to dilution process of the amount of rain. EC/RF ratios decrease from summer months to monsoon as the accumulation of salts during dry periods is drained off with the progress of monsoon rains. Visakhapatnam records higher ionic contents than other stations in India due to highly polluted industrial atmosphere. The ionic contents for Ca, Na, K and a are possibly increasing with time at Visakhapatnam.